Implementasi Nilai-Nilai Moderasi Beragama dalam Al-Qur'an dan Pengukuhan Desa Sadar Kerukunan di Kota Banda Aceh - Faisal, Muhammad (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The life of the Indonesian people, which consists of ethnic, cultural and religious differences, tends to experience several dynamics. These dynamics often lead to disputes and disputes, so that serious attention is needed from the government. So far, several efforts have been made, including forming or strengthening harmony-conscious villages, as has been done by the Banda Aceh City Government. The harmony-aware village was given to two villages, namely Kampung Mulia Village and Peunanyoeng Village, of course based on the indicators that were used as conditions for awarding the award. On the other hand, the Central Government through the Ministry of Religion of the Republic of Indonesia sparked a concept to create harmony in people's lives namely